Вплив аспірину на загальні адаптаційні реакції та тимус в експерименті - Радченко, О.М. (Медична гідрологія та реабілітація, 2010)
В эксперименте на крысах изучено влияние аспирина на массу тимуса, его морфометрию, гистологию и формирование общих неспецифических адаптационных реакций. Было выявлено уменьшение количества благоприятных типов реакций (спокойной и повышенной активации). Использование аспирина сопровождалось гистологическими и морфометрическими признаками атрофии тимуса. Это свидетельствует про угнетение иммунной системы и должно учитываться в клинике. Перспективным является экспериментальное изучение животных, которые не прореагировали на аспирин для определения возможных механизмов аспиринорезистентности. The influence of aspirin on thymus mass, morphometry, histology and common adaptive reactions forming was studied in experiment on rats. It was established that aspirin leads to decrease of favourable types of adaptive reactions (quiet and increasing activation). Using of aspirin was accompanied by histological and morphometrical signs of thymus atrophy. That data shows immune function depression and must be taking into clinical consideration. Perspective scientific direction is studying of animals which did not react to aspirin. It can explain mechanisms of aspirin-resistance.